Self-Efficacy, Pelatihan, dan Lingkungan Kerja terhadap Kinerja Perawat RSUD Tapan - Diki Okta Dwinasa; Febsri Susanti (ARZUSIN, 2025)
Initial observations at RSUD Pratama Tapan identified issues in nurse performance, including delayed task completion, low initiative, and ineffective internal communication. These conditions highlight the need to examine the factors influencing nurse performance. This study aims to analyze the effects of self-efficacy, training, and work environment on nurse performance at RSUD Tapan. A quantitative approach was applied using a survey method, with data collected through questionnaires distributed to all 42 nurses using total sampling. Data were analyzed using multiple linear regression to test the influence of each independent variable on the dependent variable. The results indicate that self-efficacy, training, and work environment all have a positive and significant effect on nurse performance. These findings emphasize that enhancing confidence through self-efficacy, providing high-quality training, and creating a supportive work environment are essential strategies for sustainably improving nurse performance. Therefore, hospital management should consider these three aspects as key components in efforts to improve the quality of healthcare services.